The wandering fibroid: a case report and an approach in reducing its incidence of future cases - Kotla, Yashika; Rajput, Disha; Jaiswal, Deepshika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Uterine fibroids are one of the most common tumours found in women of reproductive age group. parasitic or wondering fibroid are rare extra uterine benign tumours. Due to its atypical presentations and locations, these tumours cause dilemma to reach to a correct diagnosis pre operatively. Here is a case report where a 44-year-old female presenting with lower abdominal pain with a prior history of laparoscopic myomectomy with a diagnosis of leiomyoma on MRI turned out to be parasitic fibroid intra operatively.